ANALISIS PENDAPATAN UNTUK MENCAPAI LABA OPERASI DENGAN METODE BREAK EVEN POINT (BEP) - Diyah Arfiana (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2017)
This study aims to understand and analyze the revenues to achieve operating profit by methods brake even point (BEP). This type of research is descriptive quantitative research, ie operating profit calculation is performed by means of documentation. The data used in this research is quantitative data. Sources of data in this research is secondary data. Secondary data in this study is a proof statement memorandum crop breeders along with the fees. According to analysis carried out can conclude that operating profit by using Break Even Point (BEP) achieve profits not so great of proceeds because of various natural factors that can affect the production of sales.